Anticoagulation-related complications and their outcomes in hemodialysis patients with acute kidney injury at selected hospitals in Ethiopia. - Hanan Muzeyin Kedir; Abdella Birhan Yabeyu; Addisu Melkie Ejigu; Tamrat Assefa Tadesse; Eskinder Ayalew Sisay (PLoS ONE)
Introduction During hemodialysis (HD), the presence of clots in the dialyzer can diminish the effective surface area of the device. In severe cases, clot formation in the circuit can halt treatment and lead to blood loss in the system. Thus, ensuring proper anticoagulation during HD is crucial to prevent clotting in the circuit while safeguarding the patient from bleeding risks. This study aimed to evaluate anticoagulation outcomes and related factors in HD patients with acute kidney injury (AKI) at selected hospitals in Ethiopia. Method A prospective, multicenter observational study was carried out between October 1, 2021, and March 31, 2022. The study encompassed all AKI patients undergoing HD at least once during the study period. Descriptive statistics were utilized to summarize the data, and multinomial logistic regression analysis was employed to identify factors associated to clotting and bleeding. Results Data were gathered from 1010 HD procedures conducted on 175 patients. Extracorporeal circuit clotting was detected in 34 patients during 39 (3.9%) dialysis sessions while bleeding incidents occurred in 27 patients across 29 (2.9%) sessions. A statistically significant association was found between both the total number of HD treatments and blood flow rate with incidents of clotting. Factors such as length of hospitalization, serum creatinine levels at admission, signs and symptoms associated with uremia, along utilization of anticoagulants or antiplatelet medications demonstrated an association with bleeding events. Conclusion Clotting affected 19.4% of participants, while bleeding occurred in 15.4%, underscoring the importance of close monitoring. The frequency of HD sessions and blood flow rate are correlated with clotting, while hospitalization duration, serum creatinine levels, uremic symptoms, and anticoagulant use are associated with bleeding events.